Towards a natural classification of Botryosphaeriales - Liu, Jian Kui (2012)
The type specimens of Auerswaldia, Auerswaldiella, Barriopsis, Botryosphaeria, Leptoguignardia, Melanops, Neodeightonia, Phaeobotryon, Phaeobotryosphaeria, Phyllachorella, Pyrenostigme, Saccharata, Sivanesania, Spencermartinsia and Vestergrenia were examined and fresh specimens of Botryosphaeriales were collected from Thailand. This material is used to provide a systematic treatment of Botryosphaeriales based on morphology and phylogeny. Two new genera, Botryobambusa and Cophinforma are introduced and compared with existing genera. Four species new to science, Auerswaldia dothiorella, A. lignicola, Botryosphaeria fusispora and Phaeobotryosphaeria eucalypti, are also described and justified. We accept 29 genera in Botryosphaeriales, with Macrovalsaria being newly placed. In the phylogenetic tree, the 114 strains of Botyrosphaeriales included in the analysis cluster into two major clades with 80 %, 96 % and 1.00 (MP, ML and BY) support, with Clade A containing the family type of Botryosphaeriaceae, and Clade B containing Phyllosticta, Saccharata and Melanops species. This group may represent Phyllostictaceae. In Clade A the taxa analyzed cluster in eight sub-clades (Clades A1-8). Clade A1 comprises three distinct subclusters corresponding to the genera Diplodia (Diplodia Clade), Neodeightonia (Neodeightonia Clade) and Lasiodiplodia (Lasiodiplodia Clade). Clade A2 clusters into three groups representing Phaeobotryosphaeria (100 %), Phaeobotryon (100 %) and Barriopsis (94 %). Clade A3 incorporates 17 strains that cluster into three well-supported genera (Dothiorella (86 %), Spencermartinsia (100 %) and Auerswaldia (63 %); the position of Macrophomina is not stable. Clade A4 is a single lineage (100 %) representing the new genus Botryobambusa. Clade A5 is a well-supported subclade incorporating Neofussicoccum. Clade A6 represents the type species of Botryosphaeria, three other Botryosphaeria species and two other genera, Neoscytalidium and Cophinforma gen. nov. Clade A7 comprises two Pseudofusicoccum species and Clade A8 has two Aplosporella species. These sub-clades may eventually require separate families but this requires analysis of a much larger dataset. Our data advances the understanding of Botryosphaeriales, there is, however, still much research to be carried out with resolution of families and genera, linkage of sexual and asexual morphs and differentiation of cryptic species.